2002
DOI: 10.1046/j.1526-0968.2002.00462.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytapheresis for the Treatment of Myeloperoxidase Antineutrophil Cytoplasmic Antibody‐Associated Vasculitis: Report of Five Cases

Abstract: To minimize the adverse effects of high-dose administration of steroids and cyclophosphamide in patients with myeloperoxidase (MPO) antineutrophil cytoplasmic antibody (ANCA), granulocytapheresis (GCAP) or leukocytapheresis (LCAP) was performed to reduce inflammation. Four patients with rapidly progressive glomerulonephritis (RPGN) and one patient with pulmonary hemorrhage due to MPO-ANCA-associated vasculitis were treated by cytapheresis. The prednisolone (PSL) dose was 0.28 ± 0.15 mg/kg/day (mean ± SD) (rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 9 publications
0
11
0
2
Order By: Relevance
“…Hasegawa and coworkers in Japan reported that in 5 MPO-ANCA type RPGN patients who were treated by GCAP or LCAP with 10 to 20 mg of oral prednisolone only, resolution of the deterioration of renal function could be achieved [42]. Furuta et al also reported a prospective study comparing LCAP and methylprednisolone pulse therapy in which they concluded that the LCAP group had significantly greater improvement of renal function [43].…”
Section: Pathogenesis Of Mpo-anca-associated Rpgn and Apheresis Methodsmentioning
confidence: 99%
“…Hasegawa and coworkers in Japan reported that in 5 MPO-ANCA type RPGN patients who were treated by GCAP or LCAP with 10 to 20 mg of oral prednisolone only, resolution of the deterioration of renal function could be achieved [42]. Furuta et al also reported a prospective study comparing LCAP and methylprednisolone pulse therapy in which they concluded that the LCAP group had significantly greater improvement of renal function [43].…”
Section: Pathogenesis Of Mpo-anca-associated Rpgn and Apheresis Methodsmentioning
confidence: 99%
“…Although the pathophysiological mechanism of ANCA‐associated vasculitis has not been clearly elucidated, in vitro studies have shown that ANCA can activate TNF‐α‐primed polymononuclear and mononuclear cells to undergo a respiratory burst with the release of reactive oxygen species, as well as degranulation of azurophil granules and secretion of pro‐inflammatory cytokines (10). As for the mechanism of the action of cytapheresis, we previously reported that productivity of inflammatory cytokines from mononuclear cells was reduced after treatment (11) and that sTNFR1, sTNFR2, IL‐1Ra, and IL‐10 levels decreased after 1 h of cytapheresis (12). In the present study we measured sTNFR1, sTNFR2 and IL1Ra at the start of cytapheresis, at completion of the procedure, and 2 h after completion.…”
Section: Discussionmentioning
confidence: 99%
“…To minimize the adverse effects of high-dose prednisolone administration in patients with UC, rheumatoid arthritis or rapidly progressive glomerulonephritis, infl ammation has been reduced by means of granulocyte and monocyte adsorption apheresis [10,11,16] . We report for the fi rst time that granulocyte and monocyte adsorption apheresis is effective in reducing urinary albumin excretion, plasma ET-1 and plasma TNF-␣ levels in patients with active UC.…”
Section: Discussionmentioning
confidence: 99%